PENCEGAHAN PERILAKU BULLYING MELALUI PENGUATAN KARAKTER TOLERANSI PADA GENERASI Z - Mohamad Anas; Galieh Damayanti; Destriana Saraswati; Albar Adetary Hasibuan (Wisesa: Jurnal Pengabdian Masyarakat, 2024)
Bullying or intolerance is still one of the problems that occurs in Indonesia. This can be seen from the continued prevalence of bullying behavior that has surfaced and gone viral on social media. Bullying cases often occur in teenagers, especially middle and high school students. One of the causes is a lack of knowledge and understanding of the definition and forms of bullying behavior and the lack of a tolerant character among teenagers. This community service is aimed at 1) Educating and training Generation Z at the Malang City High School level in identifying problems of bullying or intolerance in their schools and 2) Instilling tolerance in Generation Z to prevent bullying behavior. The target of the service is Malang City high school students. Community service is carried out through the community development method. Service implementation is carried out through character dissemination activities by inviting resource persons from the OASE Institute. Activities are carried out through three stages: social preparation, implementation, and evaluation. The result of the implementation of the service is the formation of a cadre of Malang City High School students who have a strong character of tolerance, as well as increased student knowledge regarding potential problems of bullying and intolerance at school. By cultivating and spreading the character of tolerance through student cadres, it is hoped that bullying behavior can be prevented among Malang City High School teenagers.